2007
DOI: 10.1158/0008-5472.can-06-3066
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin, a Dietary Component, Has Anticancer, Chemosensitization, and Radiosensitization Effects by Down-regulating the MDM2 Oncogene through the PI3K/mTOR/ETS2 Pathway

Abstract: The oncoprotein MDM2, a major ubiquitin E3 ligase of tumor suppressor p53, has been suggested as a novel target for human cancer therapy based on its p53-dependent and p53-independent activities. We have identified curcumin, which has previously been shown to have anticancer activity, as an inhibitor of MDM2 expression. Curcumin down-regulates MDM2, independent of p53. In a human prostate cancer cell lines PC3 (p53 null ), curcumin reduced MDM2 protein and mRNA in a dose-and time-dependent manner, and enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
176
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(184 citation statements)
references
References 43 publications
8
176
0
Order By: Relevance
“…The cells were collected at the indicated times post-transfection and lysed in Nonidet P-40 lysis buffer containing a protease inhibitor mixture from Sigma. Cell lysates were used for immunoblotting as described elsewhere (32).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were collected at the indicated times post-transfection and lysed in Nonidet P-40 lysis buffer containing a protease inhibitor mixture from Sigma. Cell lysates were used for immunoblotting as described elsewhere (32).…”
Section: Methodsmentioning
confidence: 99%
“…We have found that (a) the combination of curcumin and gemcitabine inhibits pancreatic cancer growth in nude mice by inhibiting NF-kB regulated gene expression, cell proliferation, and angiogenesis [144]; (b) the combination of curcumin and docetaxel is effective against human ovarian cancer in nude mice [142]; (c) curcumin can suppress the growth of human glioblastoma in rodents [77]; and (d) curcumin sensitizes colon cancers in nude mice to oxaliplatin [137]. In addition, other recent studies have shown that curcumin sensitizes prostate cancers to chemotherapeutics and radiation by downregulating expression of the MDM2 oncogene [82]. Together, these in vivo animal studies clearly suggest curcumin's anticancer potential when administered either alone or in combination with currently employed chemotherapeutic agents or radiation.…”
Section: Curcumin Exhibits Antitumor Activity In Animalsmentioning
confidence: 99%
“…By apparently inhibiting the induction of steady-state transcription levels of ICAM-1, VCAM-1 and E-selectin, curcumin may be interfering detrimentally with the TNF-a-induced signaling event at an early stage. Additionally, curcumin has been shown to mediate its anticancer, chemosensitive, and radiosensitive effects via activation of p53 and simultaneous downregulation of MDM2 oncogene expression via the PI3K/mTOR/ETS2 pathway in human prostate cancer (PC3) and colon cancer (HT-29) cell lines [82,83] and to induce apoptosis and nuclear translocation and activation of p53 in human neuroblastoma cells [84].…”
mentioning
confidence: 99%
“…Curcumin has been shown to be anti-tumourigenic in different cancer cell types, including prostate cancer cells and human pituitary tumour cells (21,22). The effect of curcumin treatment on the proliferation and apoptosis of A549 cells was determined by MTT and apoptosis assays, respectively.…”
Section: Resultsmentioning
confidence: 99%